A system of inculcating national values in students through the use of examples of folklore - Pirmanova, Aziza (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The article deals with the issues of spiritual and moral education of the younger generation in folklore: human values, patriotic education, friendship, brotherhood, harmony, diligence, love of profession, definition of good and evil, the consequences of good and bad words, honesty, truthfulness, nobility , focuses on the scientific study of categories such as justice, fairness and dishonesty, the importance of brotherhood and brotherhood, bravery and cowardice, rudeness, hospitality and hospitality